The STUDENTS’ PERCEPTIONS ON USING GOOGLE CLASSROOM AS MEDIA FOR LEARNING ENGLISH - Hasma Putri, Noni Ayu (ELLTER Journal, 2024)
Learning English would be more helpful when including technology. In this digital era, technology becomes a crucial part to support teaching and learning process. The aim of this research was to find out the students’ perceptions on the use of Google Classroom as a learning media for the tenth-grade students at SMKN 1 Pemangkat. The researcher would like to know the students’ perceptions on using Google Classroom as a media for learning English. The researcher applied descriptive quantitative method. The researcher applied that method to describe the students’ perceptions on using Google Classroom as a media for learning English. The data for this research was obtained via the use of a questionnaire. Tenth grade students of SMKN 1 Pemangkat took part in this research. The results of the study reveal that students perceived Google Classroom as a learning platform that facilitated students’ needs, and it raised students’ interest and motivation in learning English.